STEM based Project Learning: How It Affects Preservice Science Teacher’s Creativity Before, During, and After Pandemic Covid-19? - Annisa Nurramadhani; Riandi; Anna Permanasari; Irma Rahma Suwarma (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
Creativity Are the important skills to face the globalization in this era. Students, especially preservice teacher should have these useful skills for make next generation are more creative, struggling with the competition between human and computers, struggling with the world condition during and after pandemic strikes, and well prepared for their work field. Some of the learning approaches have been applied in the courses to construct their creativity, one of them, are STEM (Science, Technology, Engineering, and Mathematics) by the project. This research’s aim is to investigate how is preservice science teacher’s creativity by the STEM based project learning before, during, and after pandemic covid-19. The method that is used is qualitative research by using class observation and quantitively count by creativity rubrics that includes creative thinking, behaviour, and products. This research is conducted in SETS learning (2nd semester in every year) by using STEM based project from the students of science preservice teacher year 2019, 2020, 2021, 2022. STEM based project learning could improve preservice science teacher’s creativity but it has differences for each class. Class 2019 has outperformed for creativity among others. While, class 2022 has less performed for creativity among others. Based on the observation, the covid-19 outbreak has high influence to this result because of the way of their learning in their high school before. Full online learning makes the biggest impact to science preservice teacher’s creativity during covid-19 outbreak.